Positive psychology for healthcare professionals a toolkit for improving wellbeing - MacFarlane, Jan; Carson, J. (Jerome) (Positive psychology in practice series, 2023)
Positive Psychology for Healthcare Professionalspresents applied positive psychology specifically for health and care staff, showcasing eleven different interventions that have proven to be effective in improving wellbeing.